2019
DOI: 10.3390/ma12060922
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hot-Pressing Temperature on Characteristics of Straw-Based Binderless Fiberboards with Pulping Effluent

Abstract: This study aimed to improve straw-based fiberboard properties without resins by adding pulping effluent as well as to investigate the difference among boards under variable hot-pressing temperatures. The characterization of fiberboards produced from wheat straw under pressing temperatures ranging from 160 to 200 °C was first described. The surface appearance, surface chemistry, thermal transitions, and mechanical performance of the boards were evaluated to investigate the effect of varying hot-pressing tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
6
3
0
1
Order By: Relevance
“…The material also emitted a distinctive odor. Similar results were also noticeable in the binderless boards made using the following raw materials: bagasse (Panyakaew and Fotios 2011), palm oil trunk (Boon et al 2013), unripe coconut husk (Araújo Junior et al 2018), wheat straw (Wang et al 2019), soybean straw (Song et al 2020), jute stick (Nitu et al 2020), and densified wood (Shi et al 2020); this could be the result of the modification of the chemical components that occurs during the heat treatment (Panyakaew and Fotios 2011;Wang et al 2019). The presence of hemicellulose degradation and extractive movement may be the cause of the darkening of the color (Shi et al 2020).…”
Section: Resultssupporting
confidence: 55%
“…The material also emitted a distinctive odor. Similar results were also noticeable in the binderless boards made using the following raw materials: bagasse (Panyakaew and Fotios 2011), palm oil trunk (Boon et al 2013), unripe coconut husk (Araújo Junior et al 2018), wheat straw (Wang et al 2019), soybean straw (Song et al 2020), jute stick (Nitu et al 2020), and densified wood (Shi et al 2020); this could be the result of the modification of the chemical components that occurs during the heat treatment (Panyakaew and Fotios 2011;Wang et al 2019). The presence of hemicellulose degradation and extractive movement may be the cause of the darkening of the color (Shi et al 2020).…”
Section: Resultssupporting
confidence: 55%
“…At this T IN , the SMS and EFFB fiber samples lost 56.24% and the EFB fiber sample lost 72.70% of their original weights. The drastically decreased weight loss curve for all samples occurred due to the decomposition of hemicellulose content in the fiber [47]. In addition, at this stage, previous studies reported that the decrease in weight loss for the samples also corresponded to the degradation of cellulose in the fiber [48].…”
Section: Thermogravimetric Analysismentioning
confidence: 63%
“…However, at a pressing temperature of more than 190 • C, the colour of the boards darkened, and energy consumption was excessive. No significant changes occurred up to 190 • C [4].…”
Section: Introductionmentioning
confidence: 86%